2018
DOI: 10.11152/mu-1323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tendinosis of the long head of the biceps tendon by strain and shear wave elastography

Abstract: SE and SWE may be useful diagnostic tools for LHBT tendinosis when considering usability, cost effectiveness, and patient preference compared to MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Elastography images, according to the different levels of strain, were displayed on the picture over a grayscale background in a color diagram that included the colors red (softest component), green (intermediate stiffness), and blue (hardest component). 4,5 SE patterns of the cartilages of all participants were interpreted by two radiologists with a common consensus. The SE color mappings of the cartilages were divided into four types: type I, predominantly blue (hardest tissue; ►Fig.…”
Section: Sonoelastography Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastography images, according to the different levels of strain, were displayed on the picture over a grayscale background in a color diagram that included the colors red (softest component), green (intermediate stiffness), and blue (hardest component). 4,5 SE patterns of the cartilages of all participants were interpreted by two radiologists with a common consensus. The SE color mappings of the cartilages were divided into four types: type I, predominantly blue (hardest tissue; ►Fig.…”
Section: Sonoelastography Featuresmentioning
confidence: 99%
“…[7][8][9] Elastography has been successfully applied to lesions of the breast, prostate, pancreas, lymph nodes, thyroid gland, liver, and tendon. [1][2][3][4][5][6] The external shape of the nasal tip is determined by the curves and contours of the lower lateral cartilages. 10 In rhinoplasty operations, cartilage grafts are commonly used.…”
mentioning
confidence: 99%
“…Sonoelastography is an ultrasound (US) imaging technique that can be used to assess the elastic properties of tissues qualitatively, quantitatively, or both through cross‐correlation and static compression methods . For sonoelastography, there are 2 primary techniques.…”
mentioning
confidence: 99%
“…For sonoelastography, there are 2 primary techniques. These elastographic techniques are strain elastography (SE), which compresses the tissues axially, and shear wave elastography (SWE), which uses waves that are generated by transducers and interact with the tissue . In some studies, it has been reported that there is a connection between the tissue elasticity and histologic features .…”
mentioning
confidence: 99%
See 1 more Smart Citation